Analisis Rasio Keuangan untuk Mengukur Kinerja Keuangan Pemerintah Daerah Kota Surabaya Periode 2021 - 2024 - Dwi Rezky Amalya Ahmad; Ajeng Tita Nawangsari (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2025)
Study analyzes the fiscal performance of the Surabaya City Regional the administration period 2021–2024 fiscal year using financial ratio analysis, which includes effectiveness, efficiency, fiscal efficiency, spending activity, and regional revenue and expenditure growth. Descriptive quantitative methods incorporate secondary Information derived from the Budget Realization Report (LRA) and financial statements. The study found that Regional Original Income contributes more than central and provincial government transfers. The average effectiveness ratio is 90.96% (quite effective), the efficiency ratio is 87.75% (quite efficient), and the revenue ratio is 151.57% (delegative). Operating expenditure dominates at 82.81%, while capital expenditure is only 17.05%. The growth ratio shows a fluctuating trend with PAD growing 42.56%, regional income 8.99%, operating expenditure 6.27%, and capital expenditure 27.30%. Overall, the Surabaya City Government's financial performance is good, with stable effectiveness and efficiency, a very high fiscal level, and positive revenue and expenditure growth, although inconsistent. However, the dominance of operating expenditure over capital expenditure Requires enhancement in order to financial management can focus more on infrastructure development and improving public services.